The Role of Learning Media in Strengthening Citizenship Education Learning in Elementary Schools - Zein, Alya Ramadhani (International Journal of Students Education, 2025)
This study aims to investigate and analyze various discussions about the role of learning media in strengthening civic education learning in elementary schools. Using literature review. By collecting and analyzing various sources of literature, such as academic articles, books, and research reports. This study adds insight into the Role of learning media in strengthening civic education learning in elementary schools. The basis implementation rights and obligations citizens and sustainability life man and glory nation and state must implemented in a way planned and structured for to make smart life nation and grow teak self and national morals is essence from civic education. The results of the study show that the role of learning media in strengthening civic education learning in elementary schools is to clarify the presentation of messages so that they are not too verbal, the dissemination of information widely, evenly, quickly, uniformly and integrally, so that the message can be conveyed according to what is intended or desired, technology can be presented logically scientifically and systematically and is able to complete, support, clarify concepts, principles or proportions.